Staying with the Crisis: A Feminist Politics of Care for Living with an Infected Planet - Krasny, Elke (Escritura e Imagen, 2020)
This essay is written in response to the COVID-19 outbreak. Proposing to stay with the crisis, this essay starts from the centrality of care under the pandemic conditions. Radical despair and radical hope are the entry points for analyzing the terms orienting the response to the crisis. War and care have emerged as key terms mobilizing powerful imaginaries. The efficacy of martial propaganda based on war-talk with its ideology of death poses a threat. Care, in particular care feminism, rooted in the ontological vulnerability of life and the recognition of the interconnectedness of the ties that bind us, inspires possibilities to imagining care taking and healing as a way of continued living with an infected planet. The infected planet refers to the current pandemic and to the much older disease of colonial racist patriarchy. Care feminism counteracts capitalist destruction and toxic human exceptionalism. Rooted in mutual interdependence and pandemic solidarity, care feminism presents a hopeful perspective for collaborative survival.
Keywords: COVID-19; infected planet; staying with the crisis; capitalism; war; care; feminism